THE USE OF THE OFF-DIAGONAL MAGNETOIMPEDANCE PHENOMENON TO BUILD SENSORS OF WEAK MAGNETIC FIELDS AND CURRENTS - L.V. Panina; N.A. Yudanov; A.T. Morchenko; V.G. Kostishyn; D.G. Krutogin; A.A. Rudenok (Физико-химические аспекты изучения кластеров, наноструктур и наноматериалов, 2013)
In the present work, the off-diagonal sensor design was advanced by utilising a complex waveform excitation produced by a microcontroller and applied to a multiple wire magnetoimpedance element. For optimised excitation the field resolution of about 70 mV/Oe was achieved. The concept of microcontroller driven sensor element could be attractive for the development of intellectual sensors.